Fenomena Main Hakim Sendiri dan Dampaknya terhadap Keamanan yang Berujung Pidana: (Sosialisasi Pengabdian Masyarakat di Kelurahan Pangkalan Jati) - Handoyo Prasetyo; Bambang Waluyo; Subakdi Subakdi; Edward Benedictus Roring (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
The phenomenon of "vigilante" is still a serious problem in various regions, including Pangkalan Jati Village. This extrajudicial action not only violates social norms, but also has the potential to threaten public order and security. This study aims to analyze the phenomenon of "vigilante" in Pangkalan Jati Village, as well as its impact on environmental security. The method used is a case study with a qualitative approach through in-depth interviews with community leaders, village officials, and victims/perpetrators of "vigilante" actions. The results of the study indicate that factors such as weak law enforcement, public distrust of the authorities, and lack of legal awareness are the main triggers for these actions. The impacts include increasing rates of violence, social divisions, and security instability. As an effort to overcome this problem, legal socialization has been carried out to the community as part of community service activities. This socialization is expected to increase public legal awareness, strengthen trust in the authorities, and encourage the community to resolve problems legally. This study concludes that legal socialization is an important step in preventing "vigilante" actions and creating a safe and conducive environment.